Proceedings of the 1st IKDD Conference on Data Sciences 2014
DOI: 10.1145/2567688.2567694
|View full text |Cite
|
Sign up to set email alerts
|

Theme Based Clustering of Tweets

Abstract: In this paper, we present overview of our approach for clustering tweets. Due to short text of tweets, traditional text clustering mechanisms alone may not produce optimal results. We believe that there is an underlying theme/topic present in majority of tweets which is evident in growing usage of hashtag feature in the Twitter network. Clustering tweets based on these themes seems a more natural way for grouping. We propose to use Wikipedia topic taxonomy to discover the themes from the tweets and use the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…After pre-processing of tweets, their clustering is the major area of concern. Initially, k-means algorithm have been proposed and used for clustering tweets (Kaleel and Abhari, 2015;Tripathy et al, 2014). But, this was convex cluster-based algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After pre-processing of tweets, their clustering is the major area of concern. Initially, k-means algorithm have been proposed and used for clustering tweets (Kaleel and Abhari, 2015;Tripathy et al, 2014). But, this was convex cluster-based algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Also, different categorization approaches for sentiment analysis were compared (Bravo-Marquez et al, 2014). On the other side, theme-based clustering of tweets was examined by using Wikipedia resource (Tripathy et al, 2014).…”
Section: Event Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theme recognition has been extensively studied in various fields, including music analysis and music information retrieval, 49 , 50 natural language processing and text analysis, 51 , 52 and computer vision and image understanding. In the domain of image understanding, theme recognition has been utilized to guide various computer vision tasks, such as painting scene recognition, 53 multi-class object recognition and segmentation, 54 and image caption generation 55 , 56 .…”
Section: Related Workmentioning
confidence: 99%
“…Tripathy, et al [5] proposed the clustering technique based on word frequency and Wikipedia topic taxonomy to find the discussed topic in the tweet. The research has revealed that the proposed algorithm has given better result than the algorithm which only involve word frequency.…”
Section: Related Workmentioning
confidence: 99%